2005
DOI: 10.1167/iovs.04-1530
|View full text |Cite
|
Sign up to set email alerts
|

Antitumoral Action of the Neurokinin-1-Receptor Antagonist L-733,060 and Mitogenic Action of Substance P on Human Retinoblastoma Cell Lines

Abstract: The findings demonstrate that substance P is a mitogen and also indicate that the neurokinin-1 receptor antagonist L-733,060 acts on both human retinoblastoma cell lines as an antitumoral agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
48
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 23 publications
12
48
0
2
Order By: Relevance
“…This is in agreement with previous studies, in which the use of SP peptide antagonists other than L-733,060 inhibited, both in vitro and in vivo, the growth of small cell lung cancer [18] , and it is also known that the nonpeptide antagonist L-732,138 exerts antitumor action on a glioma cell line [29] . Finally, our observations are in agreement with recent findings showing that L-733,060 has antitumor activity against other human cancer cell lines such as neuroblastoma, glioma, melanoma, retinoblastoma and pancreas adenocarcinoma [9,11,12,20] . It should be noted that in cell lines as different as those mentioned above, as well as in gastric and colon adenocarcinoma, the same NK-1 receptor antagonist (L-733,060) elicits growth inhibition.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with previous studies, in which the use of SP peptide antagonists other than L-733,060 inhibited, both in vitro and in vivo, the growth of small cell lung cancer [18] , and it is also known that the nonpeptide antagonist L-732,138 exerts antitumor action on a glioma cell line [29] . Finally, our observations are in agreement with recent findings showing that L-733,060 has antitumor activity against other human cancer cell lines such as neuroblastoma, glioma, melanoma, retinoblastoma and pancreas adenocarcinoma [9,11,12,20] . It should be noted that in cell lines as different as those mentioned above, as well as in gastric and colon adenocarcinoma, the same NK-1 receptor antagonist (L-733,060) elicits growth inhibition.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, in vitro and in vivo studies have demonstrated that SP antagonists inhibit the growth of both small cell lung cancer and glioma [18,19] . Recently, we have also demonstrated that L-733,060 shows antitumor activity against human neuroblastoma, glioma, melanoma, retinoblastoma and pancreas carcinoma cell lines [10][11][12]20] . However, to our knowledge no study has been carried out on the antitumor effect of the potent and long-acting NK-1 receptor antagonist L-733,060 against human gastric 23132/87 and colon adenocarcinoma SW-403 cell lines.…”
Section: Introductionmentioning
confidence: 95%
“…SP, an undecapeptide of the tachykinin peptide family, regulates multiple biological functions by binding to the NK-1 receptor (NK-1R), including cardiovascular and respiratory mechanisms, sensory perception, and response to stress, among others (7)(8)(9)(10). However, one of its most important functions is related to its action as a potent mitogen on some precancerous epithelial lesions and some human cancer cell lines, e.g., glioma, retinoblastoma, neuroblastoma, melanoma, and laryngeal carcinoma as previously reported by our group (6,(11)(12)(13)(14)(15)(16)(17). These observations suggest that SP may play a role in cancer development by acting as a promoter of cell growth.…”
Section: Introductionmentioning
confidence: 86%
“…Studies indicate, however, that the effect of SP is dependent on the tumor model in which it is examined. While, in some models, SP has been found to stimulate tumor growth, other studies have documented the opposite effect (6)(7)(8)(9)(10)(11)(12)(13)(14)(28)(29)(30)(31). For example, it has been demonstrated that pre-treatment of mice with SP protects against melanoma growth by inducing anti-tumor immunity.…”
Section: Discussionmentioning
confidence: 99%